Quantitative study of absorbable organic halides (AOX) residual in natural fiber-containing-fabric in Thailand - Chucheepchuenkamol, Chanakarn; Promson, Orawan; Hongsri, Korpong (Bulletin of Applied Sciences, 2023)
AOX is a product from the reaction between lignin in plant fibers and chlorine or chlorine-containing compound which occurs during the bleaching process. This compound is stable, difficult to be broken down and could be accumulated in living things, which are resulted in gene damaging, irregular growing of plants and endocrine system of animals. The detection and reduction of residual AOX compound become an issue in textile industries, which is produced during the bleaching process. The limited amount of residual AOX compound on the fabric and factory wastewater are legally indicated in many countries, but not in Thailand. This research aims to study and collect the quantitative data of remaining AOX compound in six common natural fibers fabrics in Thailand, which are unbleached cotton, bleached cotton, bleached jeans, linen, muslin, and polyester-cotton blending. The water extraction was done using Soxhlet extraction and the amount of AOX compound was determined by following the ISO 9562 procedure. The study revealed that the bleached cotton contained the highest amount of remaining AOX compound, which was 56.34 milligrams per kilogram of dried sample. On the other hand, the polyester-cotton blending contained the lowest amount of remaining AOX compound, which was 7.73 milligrams per kilogram of dried sample. Compared to the criteria that stated in Global Organic Textile Standard (GOTS), which is supposed to not more than 5.00 milligrams per kilogram, the residual amount of AOX compound of all six fabrics is higher.